Investigating the Effects of Two Different Diets on Carcass and Meat Quality Traits of Chato Murciano Pigs - Begoña Peinado; Laura Almela; Nelson Duchi; Angel Poto (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
For this study, 40 castrated male pigs of the Spanish autochthonous Chato Murciano breed were used to evaluate the effects of two diets. One group of 20 pigs was fed a high protein/low fat (HP/LF) diet and slaughtered at 125.03 kg LW. The remaining 20 pigs were fed a low protein/high fat (LP/HF) diet and slaughtered at 121.91 kg LW. Dietary effects on carcass and meat quality traits were investigated. The Longissimus lumbar (Ll) muscle was used to collect meat samples. The HP/LF diet resulted in a faster growth rate and greater daily weight gain, and measurements in the Longissimus lumbar muscle revealed higher values of ultimate pH (pHu), colour parameters, and Ca, Mg, Zn, K, and Na content. The LP/HF diet resulted in higher Fe and Cu values. The difference in Ll muscle intramuscular fat (IMF) levels was significant, with values of 3.21 percent in the HP/LF group and 11.00 percent in the LP/HF group; however, there were no differences in dorsal fat thickness measurements. The IMF fatty acid composition was 42.43 and 42.29 percent saturated fatty acids (SFA), 50.34 and 51.35 percent monounsaturated (MUFA), and 7.20 and 6.24 percent polyunsaturated fatty acids (PUFA) for the HP/LF and LP/HF groups, respectively, with only statistically significant differences in MUFA levels (P 0.05). The aim of this work was to investigate the effect of two different diets (high protein-low fat versus low protein-high fat) on carcass and morphometric parameters, meat quality and mineral and fatty acid composition in pigs of the breed Chato Murciano pure.